Spectral-domain optical coherence tomography finding of acute retinal pigment epitheliitis - Li, Yi-Hsuan (Taiwan J Ophthalmol, 2019)
Acute retinal pigment epitheliitis (ARPE) is a rare, transient macular disorder affecting healthy young adults. We describe the morphologic appearance of the retina by spectral-domain optical coherence tomography (SD-OCT) and to evaluate both the anatomic changes and the functional visual acuity changes over time in the course of disease. A 35-year-old healthy male presented with 1-week history of sudden-onset bilateral central scotoma with blurry vision. He denied trauma, excessive sun exposure, or drug abuse history or alkyl nitrites before. The medical and ocular examinations were unremarkable. The best-corrected visual acuity (BCVA) was 20/200 (OU) at the initial visit. Slit-lamp examination result was normal. Fundus examination revealed subfoveal yellowish lesions with a halo-like pigment in both eyes. The SD-OCT imaging showed subtle disruption of the retinal pigment epithelium (RPE) and abnormal hyperreflectivity throughout the full thickness of the foveola in both eyes. Six weeks later, the BCVA improved to 20/30 (OU) without any treatment. Six months later, the BCVA observed deteriorated to 20/50 (OU). SD-OCT demonstrated ellipsoid zone and cone outer segment tips line defects at the fovea with sharply defined borders. One year later from the initial visit, the BCVA improved to 20/20 (OU), but persisted macular microhole presents on the SD-OCT. The patient was followed for 1 year without any treatment. Thereafter, we noted that in the case of poor initial visual acuity, external limiting membrane, or outer nuclear layer involvement, as determined by SD-OCT, at the baseline might need longer time for visual acuity. The natural course of ARPE may involve the demonstration of a minor outer retinal defect that is similar to a macular microhole. In ARPE, like SD-OCT findings, the location of the initial lesion is the photoreceptor outer segments. It is not just limited to the RPE.